2017
DOI: 10.1080/16549716.2017.1270816
|View full text |Cite
|
Sign up to set email alerts
|

‘Life under the tent is not safe, especially for young women’: understanding intersectional violence among internally displaced youth in Leogane, Haiti

Abstract: Background: Haiti’s 2010 earthquake devastated social, health, and economic infrastructure and left 2 million persons homeless. Over 6 years later 61,000 people remain displaced, most lacking protection, services, and durable solutions. Structural contexts elevate risks of gender-based violence (GBV) targeting internally displaced (ID) girls and women. Objective: We used an intersectionality framework to explore lived experiences and understanding of violence among ID young men and women in Leogane, Haiti. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 27 publications
(47 reference statements)
3
32
0
Order By: Relevance
“…We also found that food insecurity was associated with increased exposure to young adulthood polyvictimization among urban refugee and displaced AGYW. This corroborates research that identifies poverty and its sequelae—including men’s frustrations with attempting to realize financial security for themselves and their families—with increased violence towards women in post-conflict Sierra Leone [55], Liberia [55], Colombia [31] and post-earthquake Haiti [27]. The high violence targeting both refugee and non-refugee AGYW in Kampala’s informal settlements calls for slum specific interventions to foster economic stability, upgrade physical infrastructure, and health and educational programs [52, 56].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…We also found that food insecurity was associated with increased exposure to young adulthood polyvictimization among urban refugee and displaced AGYW. This corroborates research that identifies poverty and its sequelae—including men’s frustrations with attempting to realize financial security for themselves and their families—with increased violence towards women in post-conflict Sierra Leone [55], Liberia [55], Colombia [31] and post-earthquake Haiti [27]. The high violence targeting both refugee and non-refugee AGYW in Kampala’s informal settlements calls for slum specific interventions to foster economic stability, upgrade physical infrastructure, and health and educational programs [52, 56].…”
Section: Discussionsupporting
confidence: 75%
“…Economic insecurity exacerbates risks of violence among refugee and displaced AGYW in complex ways. Forcibly displaced AGYW may engage in transactional sex to support individual and family survival [27, 28], in turn, transactional sex may elevate exposure to violence [29, 30]. Economic insecurity may challenge men’s traditional expectations of gendered roles as the breadwinner, in turn contributing to IPV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between violence and economic dependence has been established in other studies with Haitian women (Fawzi et al, 2005, Gage andHutchinson, 2006;Hunter et.al, 2011;Logie et al, 2017). Research has demonstrated that interpersonal partner violence is very common (Logie and Daniel 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Especially interesting examples of papers that take an intra-categorical perspective are Logié’s paper exploring the experiences of violence among internally displaced youth in Haiti [15]; and Shannon et al’s analysis of gender, violence and health in the Amazon of Peru [16]. The first, because it focuses on a category of oppression that has not yet received much attention: displacement.…”
mentioning
confidence: 99%